2018
DOI: 10.1002/biot.201700696
|View full text |Cite
|
Sign up to set email alerts
|

Transient Expression of Human Cytochrome P450s 2D6 and 3A4 in Nicotiana benthamiana Provides a Possibility for Rapid Substrate Testing and Production of Novel Compounds

Abstract: Employment of transient expression of foreign genes for bioconversion of pharmaceutically valuable low-molecular-weight compounds, including plant secondary metabolites, is an enticing trend still scantily explored in plant biotechnology. In the present work, an efficient protocol for rapid assessment of synthetic and plant-derived metabolites as potential substrates for human P450s (CYP2D6 and CYP3A4) via Agrobacterium-mediated transient expression in Nicotiana benthamiana is put forth. Animal P450s with broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Loratadine was selected in our present study, not only because of its routine use and determinant role of CYP2D6 on its metabolism, but also the ethical reason. Although CYP3A4, CYP2D6, and CYP2C19 are involved in the metabolism of loratadine ( Yumibe et al, 1996 ; Ghosal et al, 2009 ), the efficiency of loratadine conversion by CYP2D6 was 4.5∼5-fold higher than that of CYP3A4 ( Yumibe et al, 1996 ; Ghosal et al, 2009 ; Sheludko et al, 2018 ) and CYP2D6*10 allele accouts for approximately 50% in Asian subjects ( Johansson et al, 1994 ). For CYP3A4, many variant alleles such as CYP3A4*1B, *2, and *3 are absent in Chinese subjects ( Walker et al, 1998 ; Sata et al, 2000 ; van Schaik et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loratadine was selected in our present study, not only because of its routine use and determinant role of CYP2D6 on its metabolism, but also the ethical reason. Although CYP3A4, CYP2D6, and CYP2C19 are involved in the metabolism of loratadine ( Yumibe et al, 1996 ; Ghosal et al, 2009 ), the efficiency of loratadine conversion by CYP2D6 was 4.5∼5-fold higher than that of CYP3A4 ( Yumibe et al, 1996 ; Ghosal et al, 2009 ; Sheludko et al, 2018 ) and CYP2D6*10 allele accouts for approximately 50% in Asian subjects ( Johansson et al, 1994 ). For CYP3A4, many variant alleles such as CYP3A4*1B, *2, and *3 are absent in Chinese subjects ( Walker et al, 1998 ; Sata et al, 2000 ; van Schaik et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for choosing loratadine as a substrate drug are as follows: 1) It is often used to treat allergic diseases in Chinese children, such as seasonal allergies and rashes ( Clissold et al, 1989 ). 2) Loratadine is known to be a substrate for CYP2D6 based on previous in vitro studies ( Yumibe et al, 1996 ; Ghosal et al, 2009 ; Sheludko et al, 2018 ). CYP2D6 is the enzyme that plays an important role in the pharmacokinetic variability of loratadine in Chinese population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the systems of stable transformation of many plants are difficult to develop, and strategies based on ectopic expression, though applicable, are expensive and time-consuming even in model A. thaliana plants. On the other hand, highly efficient systems of transient expression have been developed for a number of Nicotiana species, including N. benthamiana and N. excelsior (Gerasymenko et al 2019), and the functions of many plant proteins have been identified and clarified using the data on transient expression of target genes in these plants (Anwar et al 2018, Ji et al 2018Sheludko et al 2018, Thodberg et al 2018, Li et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that gene engineering approaches, which usually entail obtaining transgenic plants, are expensive and time-consuming. In this connection, researchers studying the functional activity, substrate specificity, and physiological role of the protein products of target genes switch from obtaining stable plant transformants to using systems of transient expression of heterologous genes in model plants, such as N. benthamiana and N. excelsior (Anwar et al 2018, Ji et al 2018, Sheludko et al 2018, Thodberg et al 2018, Gerasymenko et al 2019, Li et al 2019.…”
Section: Introductionmentioning
confidence: 99%